City of Strangers : Gulf Migration and the Indian Community in Bahrain - Gardner, Andrew, 1969- (Book collections on Project MUSE., 2010)
Exploring the everyday experiences of workers from India who have migrated to Bahrain, this study contributes significantly to our understanding of politics and society among the Persian Gulf states and of the migrant labor phenomenon that is an increasingly important aspect of globalization.